Defining A Unit of Translation In A Context - Tursunov E.U, (European Journal of Life Safety and Stability (2660-9630), 2022)
the article is dedicated to define the units of translation in the context. The author cites various scientists’ opinions in defining the units of translation. Examples for defining the units of translation in the language of translation are given.